Non-alcoholic chronic calcific pancreatitis in a patient of celiac disease: a rare presentation - Gupta, Saurabh; Gupta, Poonam; Chetiwal, Rajesh; Rastogi, Priyank; Kumar, Amit; Kumar, Rajat (International Journal of Advances in Medicine, 2019)
Celiac disease is a common malabsorptive disorder in the Indian subcontinent and autoimmune dysfunction of thyroid and pancreas is frequently encountered along with. Chronic Calcific pancreatitis is a unique entity commonly seen in alcoholics but very rare in a patient of celiac disease. This case report includes the interesting constellation of calcific pancreatitis with celiac disease in a young adult male patient known case of insulin dependent diabetes and hypothyroidism. We believe it to be the only case report from north India. A 32 year old Indian male patient known case of Diabetes and hypothyroidism presented with features of malabsorption and was diagnosed with Celiac disease and calcific pancreatitis on imaging. The symptoms and insulin requirement also improved with the treatment of Celiac disease. Although a common involvement of pancreas in celiac disease, calcific pancreatitis is a rare finding and improvement of both the insulin requirement and malabsorptive symptoms with the treatment of celiac disease and pancreatitis vice-a-versa.